Some Basic Thesis of Socialism - Lenin on the State and The Applica in Vietnam - Pham, Hong Thai (H. : ĐHQGHN, 2020)
The essay focuses on explaining the basic issues of Marxism - Leninism about: the nature of the state, the dictatorship of the proletariat, the socialist state, the viewpoint of organizing the exercise of power State and application into Vietnamese conditions through historical periods through analysis of Constitutional provisions and practices